Hydrology of Al-Amara Dam and its role in water management (Journal of the College of Basic Education, 2024)
The research delved into the significance of the AL-Amara Dam, a crucial regulatory dam on "the Tigris River" in Maysan Governorate. Unlike storage dams, its primary purpose is to manage the flow of "the Tigris River" by supplying water for irrigation in Maysan Governorate. The dam achieves this by elevating the water level upstream, facilitating increased volume and efficiency of water supply to the (AL-Kahlaa, AL-Mishrah, AL-Battira, and AL-Arid) canals, meeting agricultural demands as needed. The study findings underscored "the Amara Dam's" pivotal role in (Tigris River) water management. By controlling water flow and absorbing flood waves, the dam effectively prevents floods and regulates water distribution to "the Tigris River's" distributaries.